The Growth Determinant in the Industrial Sector Featured in East Java Province (JEJAK, 2015)
This article aims toanalyzethe main determining factorof growthof industrialsector, especiallythe small scale industriesin East Javaover the past decade. Using theofthe Cobb-Douglas production functionapproach, this research assessedinputfactorconsisting oflabor, capitalandrawmaterials.This study used apooling regression modelto estimate the coefficient of production function fromfourgroups ofselected industries namely:the food industry, textile industry, wood industryandpaperindustry. The results showedthat the sourceof growthfor the industryisstilldominatedbythe physicalgrowth ofinputandnot byproductivity growth. As a result, in the long rungrowth ofthe industry is difficulttobesustainable and relativelyvulnerable toeconomic shocks. Based onthese findingssuggested thatpolicy makersfocus more onefforts toimprove the quality ofinputs, in particularinputqualityhuman resourcesor labor.